Unchained voices : an anthology of Black authors in the English-speaking world of the eighteenth century - Carretta, Vincent (University Press of Kentucky, 2004)
Vincent Carretta has assembled the most comprehensive anthology ever published of writings by eighteenth-century people of African descent, capturing the diverse experiences of blacks on both sides of the Atlantic--America, Britain, the West Indies, and Africa--between 1760 and 1798. --from publisher description.